Feed restriction in early life modifies the colonic epimural bacterial community and feed efficiency traits during the fattening period of merino lambs - Frutos J.; Andrés S.; Yáñez Ruiz D.R.; Santos A.; Benavides J.; Santos N.; Giráldez F.J. (Innovation for sustainability in sheep and goats, 2019)
Bacteria firmly attached to the gastrointestinal epithelium during early life show a significant impact on nutrient processing, immune-stimulation, health and feed efficiency traits during the entire life of lambs. Thus, the aim of the present study was to describe the changes in the colonic epimural bacterial community of fattening lambs promoted by different levels of nutrition during the suckling phase trying to shed some light on the underlying mechanisms behind different feed efficiency traits. Twenty four merino lambs (average LBW 4.81 ± 0.256 kg) were used, twelve of them (ad libitum, ADL) being kept permanently with the dams whereas the other group (restricted, RES) was separated periodically from the dams and milk restricted. After weaning all the animals were penned individually, offered the same complete pelleted diet at a restricted level (35 g/kg LBW to ensure no differences of dry matter intake) and slaughtered with a target body weight of 27 kg. During the fattening period, lower gain:feed ratio (0.320 vs. 0.261, P < 0.001) was observed for the RES group. Additionally, an increment of Prevotella sp. was detected in the colonic epimural bacterial community of RES, whereas Proteobacteria was decreased. However, the colonic gene expression of toll-like receptors and cytokines (ΔCq), immunohistochemistry parameters (counts of lymphocytes T, B) and IgA levels (pg IgA/μg total protein) were not modified. In conclusion, the level of nutrition during the suckling phase promoted changes in feed efficiency traits and colonic epimural bacterial community that were not related to the immune response at this level.
2. Joint Seminar of the Subnetworks on Nutrition and on Production Systems of the FAO-CIHEAM Network for Research and Development in Sheep and Goats, 2017/10/03-05, Vitoria-Gasteiz (Spain)